An empirical assessment of consumption practices in a revolutionary epoch : the case of Egypt and Libya - Al-Abdin, Ahmed (2015)
The aim of this thesis was to determine the impact of the recent and ongoing Arab Spring phenomenon on consumption practices in Egypt (Cairo) and Libya (Tripoli). The purpose behind the research was to empirically analyse how the Arab Spring has been driven by consumption and the extent to which consumption has been affected by the Arab Spring. A study was conducted between March-April 2013 in two of the main cities associated with the Arab Spring; Cairo (Egypt) and Tripoli (Libya). Retrospective accounts were obtained to capture citizens past experiences, present experiences and future expectations in order to develop a greater understanding of changing consumption practices. This thesis is grounded firmly in the marketing discipline as much as it is in the social sciences, particularly since the consulted literature is of an interdisciplinary nature and the Arab Spring phenomenon is not only of interest to marketing academics and practitioners but also policy makers and sociologists alike. Change is central to this thesis and citizens are considered the anchor of change. The main findings to emerge from this research are that consumption was a call for the revolution but also a cause of it. Two streams of consumption have been identified. These are conservative and conspicuous consumption. While citizens in Cairo have become more conservative in the present epoch (time of data collection March-April 2013), Libyans have become more conspicuous and are excited to try new modes of consumption. Furthermore, a contention raised in this thesis is that marketing operations in times of flux are often neglected. However, the findings demonstrate that there is a greater opportunity to capitalise on new clientele in a state of flux and amidst the instability and insecurity. As a result of the data collected in flux, this study would seem to have particular value and interestingess in the marketing discipline and beyond. Contributions made in this thesis are of a revelatory nature due to the combination of multiple theoretical lenses and the findings marking a very early empirical contribution across the social science disciplines in understanding the impact of the Arab Spring on consumption practices as well as the development and ongoing epiphenomenal state of flux in the Middle East. To the author’s best knowledge, this study is the first to conceptualise the revolutions within the marketing discipline. The findings may be transferred to other contexts and settings to examine other societies in a state of flux such as Ukraine, Syria and Iraq. A conceptual framework is used to illustrate practices in flux. Emergent themes are proposed via a conceptual model to demonstrate how flux influences consumption practices. Moreover, a novel and unusual methodological approach is used by combining a systematic literature review (SLR) as an entry point into the literature alongside grounded theory methods to study matters of consumption practices.
HydraID: hull:12267 Hydra Discover Access Group: public ETD Collection: ETDBusinessSchool
Keywords: Business